Legal Problems and Implications of Cannabis Plants in Indonesia - Mangar, Irma; Lesmana, Ryan Fachryan; Ridho , Muhammad Rosyid (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
Legal protections regarding the cultivation and use of cannabis for medicinal purposes remain ambiguous. So that there are a lot of discoveries of prohibited Cannabis plants (ganja) in Indonesia that do not have clarity on the procurement of these prohibited trees. Therefore, the Government of Indonesia needs to reform the implementation of narcotics policy in accordance with the human rights principles contained in the Constitution of the Republic of Indonesia. The purpose of this research is for readers to get a complete picture of the reasons behind the criminalization, decriminalization or legalization of cannabis plants. The method used is The type of data used in this study is normative research Normative law research has a tendency to image law as a prescriptive discipline where only looking at law from the perspective of its norms which of course is descriptive, this research is carried out in real conditions with the aim of being able to find existing facts to be used as data filler in this study so that later it will also be found the point of solving the problem.